2022
DOI: 10.1111/vcp.13110
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non‐absorbent hydrophobic sand litter on the urine protein‐to‐creatinine ratio in feline urine

Abstract: Background Proteinuria can be quantified through the measurement of the urine protein‐to‐creatinine ratio (UPC). Voided urine samples in cats are often exposed to a non‐absorbable litter substrate prior to collection and urinalysis. Little is known about the effect exposure to such substrates has on pre‐analytical variability of UPC measurements. Objectives The aim of this study was to assess agreement between UPC measurements from urine obtained by cystocentesis before and after exposure to non‐absorbent hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In 25% of study cats, a higher proteinuria substage was assigned to the same cat when cystocentesis was performed. It is unlikely that protein binding to the nonabsorbent cat litter caused a decrease in UPC in voided urine, because studies have shown that UPC is not affected by contact with nonabsorbent cat litter 21,22 . The increased storage time (1‐15 hours) of voided urine compared to cystocentesis samples also is not thought to be the cause of lower UPC results in voided urine, because a study in cats has shown that the UPC remains stable after storage of urine for 1 day, even at room temperature 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In 25% of study cats, a higher proteinuria substage was assigned to the same cat when cystocentesis was performed. It is unlikely that protein binding to the nonabsorbent cat litter caused a decrease in UPC in voided urine, because studies have shown that UPC is not affected by contact with nonabsorbent cat litter 21,22 . The increased storage time (1‐15 hours) of voided urine compared to cystocentesis samples also is not thought to be the cause of lower UPC results in voided urine, because a study in cats has shown that the UPC remains stable after storage of urine for 1 day, even at room temperature 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Current ASCVP guidelines for method comparison recommend pairing regression evaluation with BA‐plot analysis 9 . The method is commonly used in the veterinary clinical pathology laboratory and published in Veterinary Clinical Pathology manuscripts 10–14 . Others have noted that the composition and interpretation of BA‐plots are not always appropriate 7,8,15 .…”
Section: Introductionmentioning
confidence: 99%
“…9 The method is commonly used in the veterinary clinical pathology laboratory and published in Veterinary Clinical Pathology manuscripts. [10][11][12][13][14] Others have noted that the composition and interpretation of BA-plots are not always appropriate. 7,8,15 This work seeks to review the common…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Recent studies have investigated preanalytical and analytical factors influencing these urinary variables, but information on biological variation of these biomarkers in cats is lacking. [10][11][12][13][14][15] This situation is in contrast to dogs, for which 1 study reported the RCV to be 35% at high UPC values (near 12) and 80% at low UPC values (near 0.5). 16 Previous articles stated that serial UPC values in cats need to differ by 90% to conclude that the level of proteinuria has increased, and that the goal of treatment in case of proteinuria is to achieve a > 90% decrease in UPC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in cats have focused on the biological variation of serum and plasma analytes, but not on UPC or USG 5‐9 . Recent studies have investigated preanalytical and analytical factors influencing these urinary variables, but information on biological variation of these biomarkers in cats is lacking 10‐15 . This situation is in contrast to dogs, for which 1 study reported the RCV to be 35% at high UPC values (near 12) and 80% at low UPC values (near 0.5) 16 .…”
Section: Introductionmentioning
confidence: 99%